Thrombopoietin-Mediated Sustained Activation of Extracellular Signal-Regulated Kinase in UT7-Mpl Cells Requires Both Ras–Raf-1- and Rap1–B-Raf-Dependent Pathways - Garcia, Josefina (American Society for Microbiology, 2001)
Thrombopoietin (TPO) regulates growth and differentiation of megakaryocytes. We previously showed that extracellular signal-regulated kinases (ERKs) are required for TPO-mediated full megakaryocytic maturation in both normal progenitors and a megakaryoblastic cell line (UT7) expressing the TPO receptor (Mpl). In these cells, intensity and duration of TPO-induced ERK signal are controlled by several regions of the cytoplasmic domain of Mpl. In this study, we explored the signaling pathways involved in this control. We show that the small GTPases Ras and Rap1 contribute together to TPO-induced ERK activation in UT7-Mpl cells and that they do so by activating different Raf kinases as downstream effectors: a Ras–Raf-1 pathway is required to initiate ERK activation while Rap1 sustains this signal through B-Raf. Indeed, (i) in cells expressing wild-type or mutant Mpl, TPO-induced Ras and Rap1 activation correlates with early and sustained phases of ERK signal, respectively; (ii) interfering mutants of Ras and Rap1 both inhibit ERK kinase activity and ERK-dependent Elk1 transcriptional activation in response to TPO; (iii) the kinetics of activation of Raf-1 and B-Raf by TPO follow those of Ras and Rap1, respectively; (iv) RasV12-mediated Elk1 activation was modulated by the wild type or interfering mutants of Raf-1 but not those of B-Raf; (v) Elk1 activation mediated by a constitutively active mutant of Rap1 (Rap1V12) is potentiated by B-Raf and inhibited by an interfering mutant of this kinase. UT7-Mpl cells represent the second cellular model in which Ras and Rap1 act in concert to modulate the duration of ERK signal in response to a growth factor and thereby the differentiation program. This is also, to our knowledge, the first evidence suggesting that Rap1 may play an active role in megakaryocytic maturation.